Stem Cells and Cancer - Majumder, Sadhan; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
Cancer is a major cause of human morbidity and mortality worldwide. Despite decades of basic and clinical research, the outcome for many cancer patients is still dismal. Although the existence of "stem-like" cells in cancer was hypothesized more than 150 years ago, recent discoveries have the potential to revolutionize cancer therapy. In particular, we now know that many cancers contain a fraction of self-renewing, drug- and radiation-resistant cells (cancer stem cells or cancer-initiating cells) and it is these cells$1 (Band not the major bulk of the tissue$1 (Bthat are the root cause for cancer initiation, relapse and metastasis. In a single volume, Stem Cells and Cancer offers up-to-date information about the role of stem cells in the development of normal and cancerous tissue, the mechanisms that differentiate normal from cancerous functions, and the use of these findings in developing mechanism-based therapies across all major types of cancer. It provides timely, cutting-edge information about cancer stem cells from the perspectives of both the basic and clinical sciences.s
Stem Cells and Cancer: An Introduction -- Molecular Regulation of the State of Embryonic Stem Cells -- MicroRNAs in Stem Cells and Cancer Stem Cells -- Cancer Stem Cells and Metastasis: Emerging Themes and Therapeutic Implications -- Stem Cells in Leukemia and Other Hematological Malignancies -- Prostate Cancer Stem Cells -- Breast Cancer Stem Cells -- Stem Cells and Lung Cancer -- Cancer Stem Cells in Colorectal Cancer -- Cancer Stem Cells and Skin Cancer -- Lineage Relationships Connecting Germinal Regions to Brain Tumors.
Keywords: Medicine; Cancer research; Oncology; Cell biology; Biomedicine; Cancer Research; Oncology; Cell Biology; Electronic books